(untitled) (International Journal of Geoscience, Engineering and Technology, 2023)
The block effect is a typical effect in reconstructed images that have been encoded by a block-based discrete cosine transform (DCT). In highly compressed images and videos, block effects are easily noticeable as a discontinuity between relatively homogeneous regions (Wenfeng, Coskun and Yongmin, 2002). The JPEG standard has long been used as a reference algorithm for compressing monochrome images, this compression could also be applied separately to color image components (RGB). The purpose of this article is to present a method for generating quantization tables for the JPEG algorithm, which reduces the blocky effect presented by the JPEG standard.